A Statistical Physics Perspective to Understand Social Visual Attention in Autism Spectrum Disorder. (August 2017) - Liberati, Alessio; Fadda, Roberta; Doneddu, Giuseppe; Congiu, Sara; Javarone, Marco A.; Striano, Tricia; Chessa, Alessandro
This study investigated social visual attention in children with Autism Spectrum Disorder (ASD) and with typical development (TD) in the light of Brockmann and Geisel's model of visual attention. The probability distribution of gaze movements and clustering of gaze points, registered with eye-tracking technology, was studied during a free visual exploration of a gaze stimulus. A data-driven analysis of the distribution of eye movements was chosen to overcome any possible methodological problems related to the subjective expectations of the experimenters about the informative contents of the image in addition to a computational model to simulate group differences. Analysis of the eye-tracking data indicated that the scanpaths of children with TD and ASD were characterized by eye movements geometrically equivalent to Lévy flights. Children with ASD showed a higher frequency of long saccadic amplitudes compared with controls. A clustering analysis revealed a greater dispersion of eye movements for these children. Modeling of the results indicated higher values of the model parameter modulating the dispersion of eye movements for children with ASD. Together, the experimental results and the model point to a greater dispersion of gaze points in ASD.